أبو عثمان المازني وجهوده اللغوية والنحوية (ممثِّلُ أهل النحو من مدرسة البصرة) - Sirfi Fatoni, Ahmad (BARA AJI: Jurnal Keilmuan Bahasa Arab dan Pengajarannya, 2025)
This research deals about Abu Usman al-Mazini’s views and efforts on the construction of the grammar rule, as he is a representative grammarian from the Bashrah school, and this research is important to do in order to reveal a linguist who has a high contribution to the construction of the grammar rule. The type of this research is qualitative research using descriptive and critical analysis. The method of data collection is the al-istima’ method with note-taking technique. The findings are as follows: (1) Abu Usman al-Mazini is strict in taking the analogy and rejects what is not consistent with it from the Arab language and some readings of the Qur'an; (2) Sibawaih obliges i’rab al-raf’i of the word “الرجل” after “أيٌّ” in the al-nida’ as in: يا أيها الرجل, because the word "الرجل" that is intended by the al-nida’, but “أيٌّ” came as an intermediary between "الرجل" and the al-nida’ letter because it is defined by the al-alif wa al-lam, and al-Mazini argues that it may be al-nashab as the adjective in the al-munada al-mufrod in: "يا زيد الظريف". This case indicates that Abu Usman al-Mazini disagrees with Sibawaih's opinion; (3) Al-Mazini denied the al-nakirah ghoiru al-maqshudah in the al-nida’ as: "يا رجلا خذْ بيدي" that sentence is said by the blind man. He does not want that theory to exist within the framework of grammar, this case refers to his extreme opinion; (4) Al-Mazini believes that some asma’u al-af’al are manshubatun with implied verbs, as maf’ulat muthlaqah; for example, هيهات وشتان are maf’ulani muthlaqani for fi’il mahdzuf, and the estimation is "بعُدَ" as if the meaning of both of them is "بُعْدًا", this situation shows his jihad regarding the rules of grammar according to his deep knowledge; (5) Al-Mazini argues that the plural of the feminine gender should be built to al-fathu with لا النافية للجنس, such as: لا مُطيعاتَ لك, with the fathu al-ta’; this phenomenon indicates his unique opinion about the rule of grammar. Keywords: Abu Usman al-Mazini; Bashrah School; Linguistic Efforts; Grammatical Efforts; Abu Usman's Idea; Protest and Cause.